Who's Who in Research : Visual Arts. - Books, Intellect (Who's Who in Research., 2013)
This volume of Who's Who in Research series offers a useful guide for current researchers in Intellect's subject area of Visual Arts. The directory holds the names, institutions, biographies and current research interests of hundreds of leading international academics as well as references to the researchers' principal articles in Intellect journals.